The synergistic effects of ischemic stroke and amyloid pathology on cerebrovascular function. (1st February 2022) - Ismail, Ozama; Pike, Martin; Zhang, Wenri; Mishra, Anusha
Abstract: Background: Stroke survivors are at four times higher risk of developing cognitive decline 1 and aging patients who carry silent infarcts are at double the risk of dementia 2 . Importantly, cerebrovascular reactivity (CVR) and neurovascular coupling (NVC) are attenuated in stroke patients 3 . As cerebrovascular dysregulation is one of the earliest changes that precede the descent into dementia in Alzheimer's disease (AD) 4, exploring cerebrovascular effects of stroke may hold the key to understanding AD etiology. Method: We optimized a model of mild ischemic stroke by performing a 30‐minute middle cerebral artery occlusion (MCAo) which yielded a small subcortical infarct. 30‐minute MCAos were performed in 6‐month old Tg2576 mice, a model of amyloid pathology, and strain/age‐matched wild types (WT). Cerebrovascular function was then tested at chronic time points. CVR to a hypercapnic challenge was quantified using arterial spin labeling magnetic resonance imaging (MRI) 4 and 8 months after MCAo. NVC was examined using laser Doppler flowmetry, 8 months after MCAo, by measuring cerebral blood flow (CBF) changes in response to hind paw stimulation. Result: 4 months after a mild ischemia, MRI showed that CVR was attenuated in both hemispheres compared to naïve mice. This attenuation was significant in Tg2576 ischemic mice. At the 8 month time point, naïve mice also showed an age‐related decline in this response, although this decrease did not reach significance, while ischemia‐exposed Tg2576 and WT showed essentially no CVR. NVC was impaired 8 months after ischemia, with this impairment being most severe in the ipsilateral hemisphere of Tg2576 mice. Conclusion: These findings indicate that whilst ischemic stroke alone may impair CBF, it can synergize with amyloid pathology to bring about earlier and more severe changes to cerebrovascular function. Future histological analyses are expected to reveal cellular changes at the neurovascular unit that may underlie these changes and their correlation to amyloid pathology. This study sheds light on the cascade of events after stroke that may trigger AD and could guide therapeutics aimed at preserving cerebrovascular function. References: (1) Levine, D.A. et al.(2015) JAMA .314, 41–51. (2) Vermeer, S.E., Longstreth, W.T. & Koudstaal, P.J.(2007) LancetNeurol .7, 611–9. (3) Salinet, A.S.M., Robinson T.G. & Panerai, R.B.(2015) J.Appl.Physiol .118, 170–177. (4) Iturria‐Medina, Y. et al.(2016) Nat.Commun .7, 11934.